Destination selection process among international higher education students in Malaysia - Bello, Yekinni Ojo (2015)
International student migration is now a multi-billion dollar business to many countries, and the global economy. Globally, over 4.1 million students seek for university education outside their home countries in 2010, and created market worth RM1, 120-1,400 billion. Various countries are taking advantage of mobility of international students to brand a tourism typology known as edu-tourism. Thus,taking advantage of this industry to boost their foreign exchange earnings. Malaysia is having her fair share for exporting university education. This form of edu-tourism product contributed RM27 billion or four percent to the Malaysia’s Gross National Income in 2009. The government of Malaysia plan to earn RM60 billion per year from edu-tourism from the year 2020, thus, creating additional jobs of about 536,000. This highlight the attractiveness and importance of international students as a potential target group to fulfilling the national goal. Explanation on why international students decide to come to Malaysia to pursue higher education,including, factors that influence this touristic travel decision informed this study. A modified synthesis model was adapted and used to develop the contemporary edutourism destination choice model (CEDCM). The CEDCM model was used to explain edu-tourist’s decision making process, and to seek various dimensions that determine edu-tourists decision at each stage of the choice process. The research sampled 1000 postgraduate and undergraduate international students who enrolled in 13 Malaysia’s public and private universities using a survey questionnaire. The research reveals that edu-tourist’s socio-cultural factor, quest for career development, and economic factor of home country are the key intrinsic and extrinsic push factors that determines their decision to study abroad. The sociocultural and economic factor of Malaysia attracted them to Malaysia, while they choose Malaysia’s university due to its institutional characteristics, and internationalisation attributes. The study further shows socio-cultural factor of edutourists as the most influencer of decision to study abroad. Socio-cultural factor of Malaysia mostly influenced their choice of Malaysia, while institutional characteristics mostly informed their choice of university. The three hypotheses in the study are significant, hence supported, while the mediation test shows a partial mediation. This study provides significant implications for the government of Malaysia, the ministry of tourism, and higher education, including, the managers of Malaysia’s education institutions to implement its useful findings in order to leap-frog the Malaysia’s tourism sector. This include continuous tourism research effort aimed at identifying intrinsic / motives of the edu-tourists to study abroad, aside their major learning motive. Government of Malaysia, and the tourism operators should make the most of the attractive socio-economic image of Malaysia for effective positioning strategy of Malaysia in the global tourism market. Design effective tourism destination marketing strategy for the country using the socio-economic platform of the country to attracting more tourists, and as well, international students. Maximise the institutional image, and internalisation reputation of Malaysia’s universities as essential tourism assets for the country to develop its tourism industry. The ministry of tourism Malaysia in collaboration with the ministry of higher education should explore a new thrust of culture-base or adventure type of tourism to attract this specific niche market of education oriented travellers. Environment and atmosphere at the Malaysia’s tourism destinations visited by students should encourage social interaction. Specific effort should be undertaken in other to promote interaction between university students and hosts, particularly in destinations, and context where tourists-host interaction was lower among other recommendations.